The Influence of Internal Customer Care Management on Service Quality - A Case of Kilombero Sugar Company Limited (KSCL) in Tanzania - Kupeni, Leonia; Magali (PhD), Joseph (IJBLE Scientific Publications Community Inc., 2022)
The study examined the influence of internal customer care management on service quality at Kilombero Sugar Company Limited (KSCL). Specifically, the study assessed how the working environment, supervisor behavior, and serving employees contributed to service quality. The study employed an explanatory research design and the survey strategy to establish a relationship between variables. A structured questionnaire was engaged to collect data from a sample of 92 randomly selected respondents. The data were analyzed using descriptive and regression analysis. The results from descriptive and multiple regression analysis found that working environment, supervisor behavior, and serving employees' behavior positively and significantly (p< 0.05) promoted the service quality at KSCL. However, the descriptive analysis portrayed favoritism in service provision for both serving employees and supervisors as reported by 52.3% and 42.6% of respondents, respectively. The study recommends that KSCL provide training to all employees on the importance of good internal customer service. It should also improve the working environment and effective communication system. Finally, KSCL should ensure that the supervisors and employees provide service without favoritism.